Opportunities, Welfare, and Social Justice: A Review of Fishkin'sBottlenecks - Maniquet, François (Journal of Economic Literature, 2017)
In his Bottlenecks: A New Theory of Equal Opportunity, Joseph Fishkin claims he presents an entirely new way of thinking about equality of opportunity. The core of the new theory is the call for opportunity pluralism, which consists in enlarging the range of opportunities available to people at every stage in life. In this essay, we discuss how successful Fishkin is at shaking the way economists think about equality of opportunity. We identify two aspects of Fishkin's theory that deeply conflict with economic theories of equality of opportunity. Those aspects have to do with the way economists interpret the ethical values of respect for preferences and responsibility. We also argue that the way Fishkin suggests to look at opportunities can help economists fill gaps in the way they define well-being and social justice. (JEL A13, D63, I31).